2020
DOI: 10.1007/s12671-020-01545-w
|View full text |Cite
|
Sign up to set email alerts
|

Mantram Repetition as a Portable Mindfulness Practice: Applications During the COVID-19 Pandemic

Abstract: Objective Mantram or holy name repetition has long been practiced in every major religious tradition. Repetition of a mantram as a mindfulness practice is helpful for stress management and resilience building. The objective of this article is to provide an overview of the key features of mantram and the Mantram Repetition Program (MRP) developed in the US Veterans Healthcare System, the evidence base for the MRP, and its applications. Methods MRP practices are portable and do not require an extended or regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 94 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…Other studies also proved that mantra can reduce insomnia, and depression enhances self-efficacy, and mindfulness. 13 Transcendental meditation which uses silent mantra also showed decrease in stress, anxiety and it also showed increased connectivity between posterior cingulate cortex and right insula results in the changes in interoceptive awareness. 14 Brain imaging studies have shown that meditation shifts the brain activity in the prefrontal cortex from the right hemisphere to the left indicating that the brain is re-oriented from a stressful mode to one of acceptance, that may indicate better contentment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also proved that mantra can reduce insomnia, and depression enhances self-efficacy, and mindfulness. 13 Transcendental meditation which uses silent mantra also showed decrease in stress, anxiety and it also showed increased connectivity between posterior cingulate cortex and right insula results in the changes in interoceptive awareness. 14 Brain imaging studies have shown that meditation shifts the brain activity in the prefrontal cortex from the right hemisphere to the left indicating that the brain is re-oriented from a stressful mode to one of acceptance, that may indicate better contentment.…”
Section: Discussionmentioning
confidence: 99%
“…11 Studies has shown that mantras, a spiritual coping mechanism are useful in stress management for people suffering with PTSD and chronic diseases and for healthcare workers as well. 17 Since SAR-CoV-2 is a heat-sensitive enveloped virus therefore, jala neti and ghrita neti or the nasal oil application using lukewarm water and oil, respectively are efficient in upper respiratory tract infections and has been proposed as a preventive method by Traditional Chinese Medicine researchers as it forms a biofilm and prevents the entry of virus. 7,32 Heat-based therapies such as steam has been found to improve physical and mental relaxation, sleep, and mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggests that yoga, mindfulness, and mantras are an effective alternative to allay fear, distress, intense worry, emotional triggers, and psychological symptoms such as depression and improves self-awareness, empathy, and the spiritual wellbeing as well. 15,[17][18][19] Therefore, this review will describe the importance and practice of yoga and its positive outcomes for community for promoting positive mental health in the crucial times of novel coronavirus disease outbreak that will be beneficial or a constructive way out.…”
Section: Online Management Of Mental Health Through Yoga During Covid-19mentioning
confidence: 99%
“…Mantra japa can be practiced at various times throughout the day, in between activities of daily living (Bormann et al, 2020), or it can be combined with meditation. Evidence indicates the practice fosters long-term psychological benefits such as the development of resilience, healthy coping, and lower depressive symptoms (Wolf & Abell, 2003), effective management of mental health conditions including post-traumatic stress disorder, and improvement in chronic illnesses such as AIDS and cancer (Oman et al, 2022). The practice also induces a deep relaxation state in the brain and body (Harne et al, 2019).…”
Section: Hindu Practices To Enhance Emotional Mental and Spiritual We...mentioning
confidence: 99%